PD-1/PD-L1 checkpoint blockade harnesses monocyte-derived macrophages to combat cognitive impairment in a tauopathy mouse model - Neta Rosenzweig (Nature Portfolio, 2019)
Blocking the PD-1 pathway was shown to be effective in amyloid beta mouse models, yet little is known about its therapeutic potential in models of tauopathy. The authors show here that blocking PD-L1, a PD-1 ligand, is similarly effective, and that both treatments reversed cognitive deficiencies, and modified disease pathology not only in an animal model of AD, but also in the DM-hTAU mouse tauopathy model, through a mechanism that involves monocyte-derived macrophages.